ASSOCIATION BETWEEN SOCIAL DETERMINANTS OF HEALTH AND TOBACCO USE IN INDONESIAN ADOLESCENTS - Shinta Restyana Widya; Dien Anshari; Evi Martha; Natalia Desiani; Yuni Syahfitri (Universitas Airlangga, 2026)
Background: Tobacco use among adolescents remains a critical public health issue in Indonesia, contributing to long-term health risks and shaped by complex social factors. Understanding these influences is essential for effective prevention strategies. Aims: This study aims to identify the Social Determinants of Health (SDOH) associated with tobacco use among Indonesian adolescents aged 10–19 years, to support evidence-based interventions and policymaking. Methods: A quantitative cross-sectional study was conducted using secondary data from the 2023 Survei Kesehatan Indonesia (SKI), involving 126.543 adolescent respondents. Data analysis included univariable, bivariable (chi-square test), and multivariable (multiple logistic regression) approaches to explore associations between SDOH variables and tobacco use. Results: Ten SDOH variables showed significant associations with tobacco use: male gender, older age, higher education, employment, marital status, lack of health insurance, low socioeconomic status, receipt of social assistance, daily exposure to secondhand smoke, and proximity of healthcare facilities to district/city levels. In contrast, ownership of the KKS and residential area type (urban or rural) were not significantly associated.. Conclusion: SDOH significantly influence tobacco use among adolescents in Indonesia. These findings highlight the urgent need for integrated, community-based policies and interventions addressing social disparities to reduce youth tobacco consumption.